2013
DOI: 10.1016/j.combustflame.2012.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Ignition behavior and surrogate modeling of JP-8 and of camelina and tallow hydrotreated renewable jet fuels at low temperatures

Abstract: Tonghun, "Ignition behavior and surrogate modeling of JP-8 and of camelina and tallow hydrotreated renewable jet fuels at low temperatures" (2012 b s t r a c tThe autoignition characteristics of the conventional jet fuel, JP-8, and the alternative jet fuels, camelina and tallow hydrotreated renewable jet (HRJ) fuels, are investigated using a rapid compression machine and the direct test chamber charge preparation approach. Ignition delay measurements are made at low compressed temperatures (625 K 6 T c 6 730 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
68
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(71 citation statements)
references
References 20 publications
3
68
0
Order By: Relevance
“…Several alternative fuels are being considered, these include coal-derived "iso-paraffinic kerosene" (IPK) [3], FischerTropsch (FT) "synthetic paraffinic kerosene" (SPK) [3], "hydro-processed renewable jet" (HRJ) derived from camelina and tallow [3,4], alcohol-to-jet fuels (ATJ), hydro-refined algal oil [5], terpene dimers (B.G. Harvey, C. Brophy, private communication, November 14, 2011), hydrogenated-pinene (B.G.…”
Section: Introductionmentioning
confidence: 99%
“…Several alternative fuels are being considered, these include coal-derived "iso-paraffinic kerosene" (IPK) [3], FischerTropsch (FT) "synthetic paraffinic kerosene" (SPK) [3], "hydro-processed renewable jet" (HRJ) derived from camelina and tallow [3,4], alcohol-to-jet fuels (ATJ), hydro-refined algal oil [5], terpene dimers (B.G. Harvey, C. Brophy, private communication, November 14, 2011), hydrogenated-pinene (B.G.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Mueller et al [18] concluded that utilizing large iso-alkanes representative of those found in real fuels could be advantageous. In a recent study on the ignition of JP-8 and hydrotreated renewable jet fuels, Allen et al [19] utilized surrogates principally composed of large mono-methylated alkanes [20] in chemical kinetic modeling simulations to predict combustion behavior of the real fuels. They suggested that utilizing a di-methylated alkane as a surrogate for the real fuels could improve predictability, if accurate chemical kinetic models were available.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, the shock tube and RCM data correlate favorably, with the exception of HRJ-5 and LINPAR 1416V where the RCM predicts faster ignition than the shock tube. This phenomenon has been previously noted [3,4], where ignition delays measured in RCMs can be shorter than observed in shock tubes for ignition delay times less than $8 ms due to preignition chemistry occurring prior to TDC, particularly for highly reactive n-paraffinic fuels such as HRJ-5 and LINPAR 1416V.…”
Section: Comparison Of Conventional and Alternative Fuels In Intermedmentioning
confidence: 92%
“…Understanding of the chemical kinetic behavior of alternative fuels, for example macroscopically exemplified through ignition delay, flame speed, and extinction limits, is needed for combustion model development. Kinetic targets for fuel characterization and model development have only become recently available in the literature for complex multi-component fuels, including autoignition studies for conventional, HRJ, and FT fuels [3][4][5][6][7]; however, little work has been performed regarding blends of conventional and alternative fuels. Additionally, the influence of fuel composition/structure on autoignition is sparse in the literature, particularly at lean conditions, that are becoming increasingly attractive for achieving reductions in production of harmful emissions.…”
Section: Introductionmentioning
confidence: 99%